Outcome of functional endoscopic surgery for chronic rhinosinusitus - Acharya, Rabin Chandra; Pradhan, B.; Thapa, N.M. (Nepalese Journal of ENT Head and Neck Surgery, 2017)
Objective: To measure the outcome of Functional Endoscopic Sinus Surgery (FESS) for Chronic Rhinosinusitis in early postoperative period.Materials and Methods: This is a prospective comparative study conducted in Ganesh Man Singh Memorial Academy of ENT-Head and Neck Studies, Tribhuvan University Teaching Hospital, Kathmandu, Nepal from November 2009 to March, 2011. Thirty cases of Chronic Rhinosinusitis diagnosed by clinical and radiological criteria were included in this study. Modified sinonasal outcome test was used to record the pre and postoperative scores and compared by using paired t- test.Results: All the cases showed significant improvement in postoperative scores in both physical and psychosocial domains of modified sinonasal outcome test. Two symptoms, concentration and misery of psychosocial domain didn’t improve significantly.Conclusion: This study attempts to measure the outcome of FESS in patients with CRS. Nepali version of SNOT-10 has been used in the Nepalese population. Significant improvement in quality of life score has been observed in early postoperative period.